From Sraddha to Nyekar: Continuity and Change in the Practice and Meaning of Sraddha in Contemporary Society - Nareswati Kintoko Budiningsih; Febrian Indar Surya Kusuma; Satria Indar Dwi Kusuma (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2022)
Borrowing the concept of the Sraddha ritual, grave pilgrimage, nyekar or similar terms that carry important values about our attachment to our ancestors as a form of respect, many negative stereotypes are pinned on those who still perform rituals which are then only seen as a mystical, futile and ancient act without knowing the true meaning of the ritual in the concept of constructive interpretation. Dworkin emphasizes that a difference of opinion usually arises because of the different interpretation bases. This study will be carried out using the interpretation theory proposed by Ronald Dworkin as an analytical tool for the grave pilgrimage ritual or Sraddha. Based on the explanation of the Sraddha concept, it will be seen the philosophical aspects underlying the existence of similar rituals that are still carried out by some people in the eyes of the Mysticism and Logic concept proposed by Bertrand Russell. The four aspects that are understood as the characteristics of a society that adheres to mysticism can be a logical explanation for the combination of traditional values and culture of Sraddha which is not only still practiced by believers but also society in general. Through the presentation of the concepts in this study, it is hoped that this can be a way to straighten out negative misconceptions or stereotypes about spiritual practitioners that have been developing a lot in society.